Perceived Family Function and Associated Predictors in Nurses: A Cross-Sectional Study - Zeng, Wen; Fang, Qian; Wang, Cui; Tong, Beibei; Li, Dan; Zou, Ziqiu; Liu, Peiyuan; Yao, Yuanrong; Shang, Shaomei (Frontiers in Psychiatry, 2022)
Background Nurses play a key role in the health care system. However, clinical nurses experience different kinds of stressors that might impact the nurses' quality of life or quality of care. Family is one of the main social support resources, and quality family function might improve the quality of care provided by nurses. However, evidence on family function in Chinese clinical nurses is quite limited. Objectives The current study was to evaluate the family function of the Chinese clinical nurses, and to explore associated predicting factors. Methods A multi-center cross-sectional anonymous online survey was carried out. Chinese Family Function Scale was used in the study. Spearman's rank correlation analysis, Mann-Whitney U test, or Kruskal-Wallis H test was performed in the univariate analysis. The pairwise comparison method was used to determine whether the difference was significant between pair groups. Categorical regression (optimal scaling regression) was the main method to analyze factors that had been confirmed to be statistically significant in the univariate analysis. Results Nineteen thousand four hundred and twenty-two nurses completed the online questionnaires. The median of the nurse's perceived family function score was three (Inter-quartile Range: IQR 2–5). The multivariate analysis showed that the highest education level (P <0.001), the hospital level (P <0 .001), rotation shift status (P <0.001), working department (P < 0.001), number of children (P < 0.001), monthly income per family member (P < 0.001) were significantly associated with family function. Moreover, the importance of the factors was the number of children (49.1%), monthly income per family member (20.7%), rotation shift status (12.4%), the highest education level (8.0%), the hospital level (7.6%), and working department (2.4%) in turn. Conclusions The family function was associated with multiple factors, which hints that managers, leaders, and government could make strategies to improve nurses' family function in order to lead nurses to make a balance between family and work. Policymakers, nursing managers, and employers should make strategies such as promoting children-care services, increasing nurses' income, educating and training enough nurses, and building a well-established system of career development to help clinical nurses improve their family function so that to improve the quality of care.